معوقات الدعوة وسبل تجاوزها في ضوء القران الكريم-نماذج من قصص الانبياء - برشاوة, الريم (University of eloued جامعة الوادي, 2021)
تناولت هذه الدراسات معوقات الدعوة الى الله تعالى من خلال القرآن الكريم، وهي محاولة للوقوف على أبرز الصعوبات التي حالت دون وصول الرسالة الدعوية سواء أكانت متعلقة بالدعاة أنفسهم أم بالدعوة، كما وضّحت طرق تجاوز هذه التحديات على الصعيد الداخلي والخارجي، ومن ثمّ عرض نماذج من القرآن الكريم لبعض من أنبياء الله تعالى ورسله كل ذلك بقصد الإفادة من التجربة النبوية في الواقع المعاصر خاصة وأن التحديات تتكرر في جوهرها وإن اختلفت في مظاهرها. وقد خلصت هذه الدراسة إلى جملة من النتائج والتي منها: أن أهم ما يساعد على قبول الناس للدعوة أن يكون العمل بالدين واقعا حيّا في المجتمع الدعوي فالعمل بالدين أكثر دعاية له، ومن أبرز التوصيات التي جاءت عقب هذه الدراسة هي أنه على دعاة العصر مهما واجهتهم من عقبات في دعوتهم أن لا يستسلموا بل يبقوا صامدين لإعلاء كلمة الحق ويجعلوا الانبياء والرّسل قدوتهم في ذلك. "These studies dealt with the obstacles of the call to God through the Holy Qur’an, and it is an attempt to find out the most prominent difficulties that prevented the arrival of the missionary message, whether it is related to the preachers themselves or the call, as well as the methods of overcoming these challenges internally and externally, and then presenting examples from the Holy Qur’an to some of God’s prophets and messengers, all of this with the intention of benefiting from the prophetic experience in contemporary reality, especially since challenges are repeated in their essence even if they differ in its manifestation and this study has concluded a number of results, one of which is that one of the most important things that helps people accept the ivitation is that working with religion is more propaganda for it, and one of the most prominent recommandation that came in this study is that the preachers of the age, no matter what they faced obstacles in their call not to give up, but rather to romain steadfast in order to uphold the word of truth and make the prophets and messengers their models in that. "
دعوة
Keywords: الدعوة - المعوقات- قصة نوح - قصة لوط - قصة الرسول محمد صلى الله عليه وسلم; The call - Obstacles - The story of Noah - The story of Lot - The story of the Messenger Muhammad, may God bless him and grant him peace